Scale-up of a programme for malaria vector control using long-lasting insecticide-treated nets: lessons from South Sudan - Emmanuel Chanda; Constantino D Remijo; Harriet Pasquale; Samson P Baba; Richard L Lako (The World Health Organization, 2014)
Problem Long-lasting insecticidal nets (LLINs) are important tools in malaria control. South Sudan, like many other endemic countries, has struggled to improve LLIN coverage and utilization. Approach In 2006, Southern Sudan - known as South Sudan after independence in 2011 - initiated a strategic plan to increase LLIN coverage so that at least 60% of households had at least one LLIN each. By 2008, the target coverage was 80% of households and the Global Fund had financed a phased scale-up of LLIN distribution in the region. Local setting South Sudan's entire population is considered to be at risk of malaria. Poor control of the vectors and the large-scale movements of returnees, internally displaced people and refugees have exacerbated the problem. Relevant changes By 2012, approximately 8.0 million LLINs had been distributed in South Sudan. Between 2006 and 2009, the percentage of households possessing at least one LLIN increased from about 12% to 53% and LLIN utilization rates increased from 5 to 25% among children younger than 5 years and from 5 to 36% among pregnant women. The number of recorded malaria cases increased from 71 948 in 2008 to 1 198 357 in 2012. Lessons learnt In post-conflict settings, a phased programme for the national scale-up of LLIN coverage may not have a substantial impact. A nationwide campaign that is centrally coordinated and based on sound guidelines may offer greater benefits. A strong partnership base and effective channels for the timely and supplementary deployment of LLINs may be essential for universal coverage.